Language Markers and Social Identity in Digital Communication Among Generation Z in Indonesia - Jayaputri, Herlandri Eka; Aziz, Muhammad Fahruddin (Applied Linguistics: Innovative Approaches and Emerging Trends, 2024)
This study examines the use of language markers in digital communication among Generation Z in Indonesia, focusing on their functions and socio-cultural implications. Using a qualitative approach, the research analyzed data from document observations, semi-structured interviews, and focus group discussions. Data analysis involved four stages: data reduction, contextual analysis, triangulation, and interpretation. The findings show that markers like “so,” “then,” “maybe,” and “I guess” serve functions such as enhancing politeness, clarifying messages, and fostering familiarity. These markers also reflect globalization’s influence, cultural values of politeness and inclusiveness, and Generation Z’s digital norms. The study illustrates how linguistic choices shape social identity, highlighting language markers’ role in effective communication. The results offer valuable insights into Generation Z’s communication practices and implications for cross-cultural and intergenerational dialogue in digital spaces